Comprehensive Study of Environmental Radioactivity - Jargalsaikhan, Munkhsaikhan (Scientific transaction of the National University of Mongolia. Physics, 2025)
Researchers at the Nuclear Research Center of the National University of Mongolia conducted environmental radiation studies to assess the levels of radioactivity in soil and water across various regions of Mongolia, including the western, central, and Gobi areas; major cities such as Ulaanbaatar, Darkhan, and Erdenet; as well as areas with uranium mines and coal deposits. As part of this work, a comprehensive methodology was developed. The findings are significant for establishing background radiation levels in Mongolia and play a critical role in radiation monitoring. This article also provides an overview of research related to air pollution, radon concentration, evaluations of external radiation exposure, and assessments of radioactivity in some food products and construction materials.